Modelling Of Gas Diffusion In Mesoporous Tin Dioxide (SnO2) As Gas Sensor In Detecting Acetone Vapour - Mohan, Khamini (Universiti Sains Malaysia, 2021)
Mesoporous semiconductor based gas sensors have been extensively researched and employed in the detection of traces poisonous and flammable gases such as nitrogen dioxide (NO2), carbon monoxide (CO), sulphur dioxide (SO2) and volatile organic compounds (VOCs) such as ethanol, methanol and acetone which are dangerous to both people and the environment. In this research, mesoporous tin dioxide based gas sensor, SnO2 is utilized due to its low cost, high sensitivity and quick response. In order to determine the most effective techniques for optimising the gas sensing properties of mesoporous SnO2, the effect of acetone concentration and operating temperature on the sensitivity of a gas sensor was investigated using a diffusion mechanism model. The gas detecting mechanism was controlled by Knudsen diffusion of the target gas through the porous film and its interaction with adsorbed oxygen, which followed a first-order reaction kinetic. In the diffusion mechanism model equation, a general expression of sensitivity, S (Ra/Rg) as a function of pre-exponential constants, α0 and k0, reaction activation energy for gas dependent, Ea, universal gas constant, R, temperature, T, concentration,